The Determination of Fetal Gender with Gestational Sac Volume Maternal Age and Body Mass Index - Aytekin Aydın; Mustafa Öztürk; Murat Gökhan Kinaş (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: In this study, we aimed to examine the effects of fetal gender on Gestational Sac Volume (GSV), maternal age and Body Mass Index (BMI) between 10 and 12 gestational weeks in order to detect the fetal gender in diseases being transferred genetically with x by using non-invasive methods. STUDY DESIGN: 37 pregnant women who came for routine antenatal controls between 10 and 12 gestational weeks were incorporated in study. The GSV was measured via transabdominal ultrasonography on those pregnant women, maternal ages were determined and BMI was calculated. Then, between 20 and 22 gestational weeks, pregnant women were taken in sonographic evaluation for sex determination. RESULTS: The average age of pregnant women was 32 (min.20 - max.41). 28 of them (76%) were pregnant in 10 weeks, 5 of them (14%) were pregnant in 11 weeks, and 4 of them (%10) were pregnant in 12 weeks. The GSV, maternal age and BMI values of all of the pregnant women were compared. No significant relationship was found between male and female fetuses in terms of GSV, maternal age and BMI values (p>0.05). CONCLUSION: We found that GSV, maternal age and BMI have no effect for determination of fetal gender which is very important for hereditary diseases in early pregnancy.